Extracellular Vesicles: New Perspectives of Regenerative and Reproductive Veterinary Medicine - Zakirova, Elena Yu; Aimaletdinov, Alexande M.; Malanyeva, Albina G.; Rutland, Catrin S.; Rizvanov, Albert A. (Frontiers in Veterinary Science, 2020)
Extracellular vesicles are released by all cell types including stem cells. Stem cell-released extracellular vesicles have therapeutic effects similar to those of their parent cells and have regenerative effects in tissues. They also have an immunomodulating effect when down-regulating some proinflammatory factors, without exerting effects on cell proliferation, modulating angiogenesis or altering cellular functions in recipient cells. Modern veterinary research explores vesicles and creates or advances methods of using them in regenerative and reproductive medicine, applications of these technologies are under development.